Socio-environmental costs: Financial quantification of carbon credits in agriculture and sustainability in the relation of produced agroenergy with used energy matrix - Andrade, Marcos; Feiden, Armin [UNESP]; Zonin, Wilson João; Besen, Fabiola Graciele; de Araújo, Tércio Vieira (My University, 2018)
The present study aimed to quantify the financial value of the carbon credits generated by the substitution of diesel fuel for biofuels in the agricultural activity, analyzing the energy matrix and the energy sources used in agriculture. Reducing greenhouse gas emissions and carbon sequestration generate credits that can be traded through financial returns. In view of this, the following problem arose: Can carbon credits stimulate change in the agricultural production model so that there is a reduction in emissions and an increase in carbon sequestration in rural areas? In addition to the financial return for the commercialization of credits, low-carbon agriculture can make use of indirect benefits such as subsidized interest financing lines and access to more demanding markets. The methodology used was the exploratory and bibliographical research by obtaining data on carbon credits and gas emissions. From this, an analysis was developed applying the qualitative and quantitative approach, measuring the financial value of the carbon credits generated in agriculture. Through these analyzes, it was possible to conclude that the socio-environmental actions resulting from the agricultural activity produce carbon credits that can be commercialized by the farmer.
Keywords: Carbon credits; Energy matrix; Socio-environmental costs